Whispers to Voices : Gender and Social Transformation in Bangladesh - World Bank (World Bank, Dhaka, Bangladesh, 2017)
Bangladesh stands out as the shining new example in South Asia of a poor country achieving impressive gains in gender equality. Between 1971 and 2004, Bangladesh halved its fertility rates. In much of the country today, girls' secondary school attendance exceeds that of boys. The gender gap in infant mortality has been closed. The scholarly work that came out of the micro credit revolution is based on large and unique data sets and high quality ethnographic work and has set a high bar for evidence-based policy proposals. Beyond a doubt, Bangladesh has made great progress in achieving gender equality and enhancing the status of women. Its success in girls' education, reducing fertility and mortality and the famed microcredit revolution are some of the gains that set it apart from its neighbors and other countries of its income level. When young women and their families were asked what this meant for them and how their lives were different from their mothers', the unexpectedly common theme was "finding a voice" or "being able to speak" or "being listened to".